Open educational practices in public higher education in Portugal - Cardoso, Paula (2014)
The main objective of this PhD research is to identify and understand the education and research practices of teachers/researchers of public Higher Education Institutions (HEI) in Portugal, as well as the influence of recommendations, initiatives and public support in the development of open educational practices. To contextualize the problem, the study involves three levels of analysis: i) macro level, in terms of guidelines on open education and open access, both at European and national levels, as well as the strategies aligned with these guidelines; ii) mezzo level, regarding public HEI in Portugal, characterizing their openness degree and support of open practices development; iii) micro level, focusing on the practices of teachers/researchers in their academic context, when playing the dual role in research and education.